Preserving kyai authority in modern society; A case study of Pesantren Cidahu, Pandeglang, Banten - Machmudi, Yon (Wacana, Journal of the Humanities of Indonesia, 2014)
A pesantren is a typical component of the Indonesian cultural heritage. Besides being thought of as one of the oldest type of educational institutions in Indonesia, pesantren have played a significant contributing role in the process of nation building in modern Indonesia. Pesantren have many roles in society in education, the economy and in the social and political fields in which pesantren alumni play a role. Currently, pesantren roles are being challenged by modernization and they have to change or transform into modern institutions in order to survive. Nevertheless, traditional pesantren continue to resists change and they insist on preserving their identity in terms of authority and student teacher relationships. This article seeks to analyse the efforts that the traditional Pesantren Cidahu in Banten makes to preserve its identity and to maintain its authority in modern society. By hanging on to modest practices, Pesantren Cidahu manages to continue to exert strong influence over its students and over the society in West Java in general.